ULTRASOUND GUIDED SUPRACLAVICULAR BRACHIAL PLEXUS BLOCK FOR UPPER LIMB SURGERY IN CARDIOVASCULAR COMPROMISED PATIENT - Temelkovska Stevanovska, Marina; Dimitrovski, Aleksandar; Panovska Petrusheva, Aleksandra; Gavrilovska Brzanov Aleksandra (Department of Anaesthesia and Reanimation, Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, R.N. Macedonia, 2025)
Introduction: We can use the supraclavicular block as a postoperative pain management approach, as an addition to general anesthesia, or as the sole form of anesthesia for upper limb surgery. For upper limb surgery, this block is a fantastic substitute for general anesthesia in patients with pulmonary and cardiac comorbidities. Case Presentation: In order to undergo surgery for a fracture of the proximal portion of his upper arm, a 66-years-old male AA was brought to the Clinic for Orthopedic Diseases in Skopje. The anesthesiologic examination revealed that the patient had diabetes mellitus type II, cardiomyopathy, untreated ischemic heart disease and wheezing and crepitations in the distal portions of his lungs. We planned the open fixation of the fracture for the patient. A supraclavicular brachial plexus block was performed as the most non-invasive procedure for perioperative treatment, taking into consideration the patient’s health. The patient’s vital indicators were normal and stable during the procedure. After receiving therapy for two days, the postoperative course was uneventful, leading to the patient’s discharge. Conclusion: If not addressed earlier, preoperative pulmonary and cardiac comorbidity increases the risk of perioperative and postoperative problems. With no postoperative problems, peripheral nerve block – in our case, supraclavicular brachial plexus block – proved to be a safe option for anesthesia management used for upper limb surgery.
Keywords: anesthesia Brachial plexus block; fracture of upper arm; postoperative complications; supraclavicular block